2021
DOI: 10.1186/s12912-021-00739-4
|View full text |Cite
|
Sign up to set email alerts
|

Work-related factors predict changes in physical activity among nurses participating in a web-based worksite intervention: A randomized controlled trial

Abstract: Background Despite the numerous benefits associated with physical activity (PA), most nurses are not active enough and few interventions have been developed to promote PA among nurses. A secondary analysis of raw data from a single-centre, three-arm parallel-group randomized controlled trial was conducted to assess whether work-related characteristics and general mood states predict changes in total weekly moderate-to-vigorous intensity PA (MVPA) and average daily step-count among nurses partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Similarly, a physical activity intervention for hospital workers revealed that the attrition rate for shift workers was significantly higher than non‐shift workers ( p = 0.01) 64 . A recent intervention aimed at increasing physical activity for nurses revealed that a subset of nurses working rotational shifts showed smaller improvements in physical activity, with authors speculating that the perception of lack of time and fatigue associated with this work schedule makes increasing physical activity harder to achieve 65 . It is clear that dedicated weight loss interventions for night shift workers are needed with careful consideration of design to address the time constraints barrier, to maximize recruitment, retention, and successful outcomes for participants.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a physical activity intervention for hospital workers revealed that the attrition rate for shift workers was significantly higher than non‐shift workers ( p = 0.01) 64 . A recent intervention aimed at increasing physical activity for nurses revealed that a subset of nurses working rotational shifts showed smaller improvements in physical activity, with authors speculating that the perception of lack of time and fatigue associated with this work schedule makes increasing physical activity harder to achieve 65 . It is clear that dedicated weight loss interventions for night shift workers are needed with careful consideration of design to address the time constraints barrier, to maximize recruitment, retention, and successful outcomes for participants.…”
Section: Discussionmentioning
confidence: 99%
“…A study to increase physical activity levels of nurses (n = 70) found that work-related factors (e.g. shift schedule and role type) predicted the change in moderate physical activity achieved 36 . Interventions to support lifestyle behaviour change need to be multicomponent to address causes of workplace stressors 36,37 additional to behavioural-based interventions aimed at mitigating the neuroendocrine abnormalities of circadian disruption [9][10][11][12][13][14][15][16]38 .…”
Section: Discussionmentioning
confidence: 99%
“…Benzo, et al ( Benzo et al, 2021 ) reported that nurses who worked day shifts spent more time standing and walking compared to those who worked night shifts, which makes sense given that most medical procedures take place during the day ( Chang and Cho, 2022 ). Shift nurses were found to engage in less moderate to vigorous physical activity on a weekly basis, demonstrating the influence of work-related factors, such as time constraints and fatigue ( Brunet et al, 2021 ). In contrast, in the emergency room, nurses took more steps (9720 ± 4072 steps) during the evening shift due to the high amount of unpredictable work ( Chang and Cho, 2022 ).…”
Section: Introductionmentioning
confidence: 99%